Identifikasi dan Karakterisasi Faktor Transkripsi DREB pada Tanaman Singkong (Manihot esculenta Crantz) Melalui Studi Bioinformatika - Ludfi Kurniawan (Fakultas Matematika dan Ilmu Pengetahuan Alam, 2026)
Cassava is a fairly productive commodity and is used as an alternative staple food and industrial raw material. This shows the potential of cassava as a prospective commodity to be developed and increase its production. However, these efforts were disrupted by the increasing expansion of dry land. The ability of cassava to grow optimally on dry land is the background for the development of cassava varieties that are resistant to drought stress by identifying drought-resistant genes. DREB is a gene that plays a role in the regulation of drought stress in plants. The identification of the DREB gene was carried out using bioinformatics analysis, including MeDREB identification, gene structure, cis-acting elements, gene location, physicochemical analysis, motifs, subcellular localization, phylogenetics, and inter-protein interactions. The results of DREB identification revealed as many as 81 genes with characteristics that all MeDREBs are hydrophilic with negative GRAVY values and are mostly localized to the nucleus. Analysis of gene structure and motifs showed that the gene structure was varied, and all DREB transcription factors had AP2 motifs. MeDREB promoter regions have varied and specific cis elements to express drought-resistant genes such as ABRE, DRE, and others. Phylogenetic analysis results show that all DREB genes are distributed throughout the DREB-containing clades of other plant species. There is one DREB clade filled by MeDREB. DREB-Dof interactions can occur due to co-factors that reside on the same promoter. The results of the overall analysis obtained three DREB gene candidates from bioinformatics analysis results, namely MeDREB-41, MeDREB44, and MeDREB-71.
Finalisasi 16 Juli 2026_Yudi
Keywords: Dehydration-Responsive Element Binding; cassava; bioinformatics